Paradise Peak - Dailey, Janet (Kensington Books, 2020)
"A desire for absolution brought ex-con Travis Alden to Paradise Peak, Tennessee. But when he finds honest work, along with a keen sense of belonging, he shelves his plan to unburden his guilty secret, instead working to rehabilitate a ranch alongside the very people his transgressions hurt the most. With the chance to create a haven for wildfire refugees, Travis seizes the opportunity to do good, to earn the respect his new boss shows him. Only Travis doesn't count on his feelings for his boss's beautiful niece."--Provided by publisher.
Sequel to: Hart's Hollow Farm.
Keywords: Ex-convicts -- Fiction; Man-woman relationships -- Fiction; Wilderness areas -- Tennessee -- Fiction; Ranch life -- Tennessee -- Fiction; Tennessee -- Fiction; Romance fiction